1985
DOI: 10.2466/pms.1985.61.3.823
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Memory for Dreams: The Role of Cognitive Skills

Abstract: Summasy.-Ontogenetic findings have suggested a relationship between selected cognitive variables, especially Block Design ability, and REM dreamrecall rates. This study investigated the extent to which such cognitive variables could account for individual differences in the REM recall of home-dream "nonreporters," defined as self-described infrequent recallers who also recorded few dreams in a dream diary. Adult male nonreporters were assigned either to a high Block Design or low Blodt Design group ( n = G eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 6 publications
(4 reference statements)
1
34
0
1
Order By: Relevance
“…From this perspective, the clinical symptom of dream cessation is caused by interference in the internal production of the visual imagery of dreaming, but it is not a consequence of amnesia per se. Intriguingly, this conclusion coincided with the early studies on children's REM dreams, which suggested that dream-recall rate is correlated with visuospatial skills (Butler & Watson, 1985;Foulkes, 1999;Foulkes, Hollifield, Sullivan, Bradley, & Terry, 1990). The dissociation between cessation of dream experiences and memory failure sounds paradoxical if one embraces the conviction that dream recall relies on one, and only one, indivisible function-namely, "memory"-which is compromised in neurological patients.…”
Section: Dissociation Between Memory Failure and Cessation Of Dream Esupporting
confidence: 51%
“…From this perspective, the clinical symptom of dream cessation is caused by interference in the internal production of the visual imagery of dreaming, but it is not a consequence of amnesia per se. Intriguingly, this conclusion coincided with the early studies on children's REM dreams, which suggested that dream-recall rate is correlated with visuospatial skills (Butler & Watson, 1985;Foulkes, 1999;Foulkes, Hollifield, Sullivan, Bradley, & Terry, 1990). The dissociation between cessation of dream experiences and memory failure sounds paradoxical if one embraces the conviction that dream recall relies on one, and only one, indivisible function-namely, "memory"-which is compromised in neurological patients.…”
Section: Dissociation Between Memory Failure and Cessation Of Dream Esupporting
confidence: 51%
“…From lesion studies (Box 3) we know that dreaming requires an intact temporo-parieto-occipital junction[22, 23] and lesions in this region also affect mental imagery in wakefulness[109]. Cognitive studies indicate that the skill that maximally correlates with dream recall in adults is visuo-spatial imagery[110]. In children, dream recall develops hand in hand with visuo-spatial imagery (Box 2).…”
Section: Are Dreams More Like Perception or Imagination?mentioning
confidence: 99%
“…Several authors (Pivik, Bylsma, Busby, Sayer, 1982;Foulkes, 1985;Butler and Watson, 1985) suggested that, since the Block Design test does not involve memory or language and since a positive relationship between visuo-constructive performance on the Block Design test and dream recall exists (Foulkes, 1985; Butler and Watson, 1985; Foulkes, Hollifield, Sullivan, Bradley, Terry, 1990), poor dream recall may be linked to a scarce ability in the perceptual decoding or creation of the dream itself.…”
Section: Mean Manual Response Times Of Non-dream Recallers (Ndr) and mentioning
confidence: 99%